Dydrogesterone usage pattern in India: a knowledge, attitude and practice survey among Indian gynaecologists - Khanna, Geeta; Dabade, Madhuri; Dutta, Sajal; Deshpande, Nitin; Mane, Girish; Shah, Chetna; Deshmukh, Girish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: There is limited data about the knowledge, perception, and routine clinical usage pattern of dydrogesterone among medical practitioners in India. Therefore, the present survey was undertaken to assess attitudes and perception/practices of obstetrician and gynaecologists towards use of dydrogesterone in the real-life setting. Methods: Total 1168 gynaecologists across India participated in the KAP survey. Sixteen questions which explored indications, dosages, duration, efficacy, tolerability and comparison were asked and results were expressed as percentages. Results: Dydrogesterone has been marketed since the 1960s and has been extensively used worldwide for the treatment of threatened miscarriage (TM) and recurrent miscarriage (RM). Dydrogesterone is approved for hormone replacement therapy (HRT), as well as pregnancy and non-pregnancy-related conditions where there is a progesterone deficiency. In the present survey, dydrogesterone 10 mg twice daily was found to be the most commonly preferred dosage by 823 (73%) gynaecologists. Poor tolerability, compliance and lower efficacy were reported as major limitations of micronized progesterone by 68% of doctors. The average clinical pregnancy rate noted at 12 weeks after Dydrogesterone usage was around 40% by majority of the doctors. However, 30% of doctors noted more than 40% of clinical pregnancy rate after dydrogesterone usage. Almost 35% of doctors reported that the average live birth rate noticed after dydrogesterone usage is around 40%. Conclusions: The present KAP survey highlights that the effectiveness and the tolerability of dydrogesterone is valued by Indian gynaecologists which accounts for its robust clinical utility.